The Influence of Interest in Choosing the Mechanical Engineering Vocational Program in Vocational High Schools - Putri Wulan Juliana; Thomas Sukardi (Journal of Educational Science and Technology (EST), 2019)
This research aimed to find out the influence of students’ interests in choosing the mechanical engineering vocational program. The research method used was descriptive quantitative. The population in this study were all Grade X students in Yogyakarta which total number were 180 respondents. The data collecting technique was using questionnaires which then was analyzed using descriptive analysis and regression. The results of this study were (1) Students’ interests in choosing mechanical engineering vocational program was high. (2) There was a positive and significant influence from students’ own understanding, family, school, and society towards students’ interests in choosing the mechanical engineering vocational program, (3) The four variables, together, have positive and significant influences towards vocational high school students’ interests in choosing the mechanical engineering vocational program in Yogyakarta..